Girl–boy differences in perceptions of health determinants and cancer: a more systemic view of girls as young as 6 years - Gay, Chloé; Deyra, Maéliane; Berland, Pauline; Gerbaud, Laurent; Pizon, Frank (Frontiers in Public Health, 2023)
Model and analyze the differences between girls' and boys' conceptions of the determinants of health and cancer, as expressed and perceived by children and adolescents.Method: Multicentric qualitative study was conducted in 5 schools (6 -11 years), 4 middle schools (11 -15 years), and 3 high schools (15 -18 years). A multi-phase protocol (phase 1 uses the e.Photoexpression© and phase 2 uses the Photonarration) enables children and teenagers to express themselves through photography and storytelling.Results: 4174 qualitative productions were produced by 1068 children, 47% girls and 53% boys, aged 6 to 18. The results show that children mention and are aware of 30 determinants of health and cancer. The 3 determinants most mentioned were "Consumption of psychotropic drugs", "Diet" and "Harmful environment". Among these 30 determinants, some are mentioned to a greater or lesser extent by girls and boys. These significant gender differences are present for 20 determinants of health and cancer.These differences evolve with age:-In elementary school (ages 6 to 11), girls give significantly more importance (p<0.05) to 11 determinants. Boys attach significantly more importance (p<0.05) to 2 determinants.-In middle school (ages 11 to 16), girls gave significantly (p<0.05) more importance to 12 determinants. Boys gave significantly (p<0.05) more importance to 1 determinant.-In high school (15 to 18 years), girls gave significantly (p<0.05) more importance to 13 determinants. There was no significant difference (p<0.05) in favor of boys for high school students.Girls also have a more systemic view of health determinants than boys. The increase in the number of determinants cited by girls is significant (p = 0.017) between the ages of 6-11 and 15-18. This gap widens with age (+1.45 determinants) for girls and (+0.68 determinants) for boys between elementary school and high school.The determinants identified as predominantly female or male, as well as age-related specificities, constitute a resource for effective preventive action, as close as possible to the needs and particularities of a population. This mapping of people conceptions could provide a decision-making aid in defining the strategic orientations of prevention policies.